Crystalline Characteristic Effect of In Situ Interaction between ZnO and Pht on Inducing β Nucleation of Isotactic Polypropylene. (27th May 2022) - Cheng, Shuya; Zhang, Kai; Xu, Guomin; Shan, Chunyan; He, Min; Qin, Shuhao; Yu, Jie
Abstract : The β -nucleating agent ( β -NA), zinc phthalate (ZnPht), was prepared from a mixture of zinc oxide (ZnO) and phthalic anhydride (Pht) during the extrusion of isotactic polypropylene (iPP). To establish the relationship between the crystalline characteristic of ZnO and the crystallization of iPP, single-crystalline ZnO (ZnO(S)) and polycrystalline ZnO (ZnO(P)) were selected and mixed with Pht, respectively, to in situ inducing the β -crystal form of iPP ( β -iPP). Compared to ZnO(S)/Pht, ZnO(P)/Pht has the selectivity of β -crystal nucleation during the crystallization of iPP; indeed, the relative content of β -crystal (k β ) improved from 18.0% for ZnO(S)/Pht/iPP to 84.6% for ZnO(P)/Pht/iPP. Moreover, the impact strength of the ZnO(P)/Pht/iPP was nearly 2.0 times greater than pure iPP; for ZnO(S)/Pht/iPP, it was approximately 1.4 times greater than pure iPP. To explain these phenomena, we propose a mechanism that the content of ZnPht generated by ZnO(P)/Pht is more than that of ZnO(S)/Pht during its in situ reaction; evidence from Fourier transform infrared spectroscopy, wide-angle X -ray diffraction, and thermogravimetric infrared spectroscope analysis was consistent with this mechanism. This study may provide a new perspective to control the crystal type of polymorphic polymer by adjusting the crystalline characteristic of the nucleating agent.